Adaptive Livelihood Strategies Among Households After the Closure of Fluorspar Mining Company in Keiyo South Sub-County, Elgeyo Marakwet County, Kenya - Bargoria, Finson Kiprop; Barasa, Francis; Chebet, Paul Sutter (Journal of Advanced Research in Humanities and Social Sciences, 2020)
The establishment and existence of the Fluorspar Mining Company created direct and indirect employment opportunities for the local population. However, the closure of mining activities within the mining area may have led to social and economic challenges for the local communities. These were widespread unemployment, poor nutrition, high crime rates and increased dependency. The study objective was to analyze the livelihood strategies among households in Keiyo South Sub-county Elgeyo Marakwet County Kenya. The study was informed by the theory of Redefinition of situation. Survey research design guided the study. The target population was all the households’ heads in the study area. The sample size was 254 respondents. A multistage sampling technique was used. Data collection methods included questionnaires, interviews, and observation and focus group discussions as the main data collection tools. Quantitative data collected was analyzed in form of frequencies and percentages and presented in form of matrix tables, charts and graphs. On the other hand, qualitative data was analyzed thematically based on the specific research objectives. The results of the study show that mining is a major propellant of economic activities in most mining areas by creating wealth, providing jobs, and stimulating business ventures for community members. Further, closure of the company acted as a major economic setback to the community as a whole. The study findings also show that majority 91(44.4%) of respondents earned an income of 4001-8000ksh while minority 7(3.4%) earned an income of between 0-500kshs. The average income per month after closure was too low since their main source of income was lost leaving them in despair. Communities and mineworkers should be involved in planning for company closure and all other matters that affect their livelihoods. How to cite this article: Bargoria FK,Barasa F, Chebet PS. Adaptive Livelihood Strategies Among Households After the Closure of Fluorspar Mining Company in Keiyo South Sub-County, Elgeyo Marakwet County, Kenya. J Adv Res Humani Social Sci 2020; 7(2): 1-8.